Економіка інформації у просторі економічних досліджень - Конохова, Зоя Петрівна (Миколаївський національний університет ім. В. О. Сухомлинського, 2018)
Статтю присвячено визначенню економіки інформації як області наукових досліджень. Відображені основні етапи розвитку поглядів на економічне втілення інформації. Визначаються основні напрями вивчення властивостей інформації як економічного явища та процесу. Наголошується на необхідності глибокого опрацювання сутності інформації як економічної категорії. Запропоновано приділити більше уваги використанню інформації у процесі розроблення та впровадження засобів державного регулювання економіки.

The article is devoted to the definition of information economics as a field of scientific research. The article reflects the main stages of development of views on the economic implementation of information. Also it`s determined the main directions of studying the properties of information as an economic phenomenon and process. And it`s underlined necessity of deep study of the essence of information as an economic category. We propose to pay more attention to the use of information in the process of developing and implementing the means of state regulation of the economy.
Economy of information in the space of economic research
Keywords: інформація; економіка інформації; асиметрія інформації; державне регулювання економіки; information; information economy; uncertainty; information asymmetry; state regulation of the economy